The Problem of Enforcement in International Law Countermeasures, the Non-Injured State and the Idea of International Community - Proukaki, Elena Katselli (2011)
This book explores the contentious topic of how collective and community issues should be protected and enforced in international law. Elena Katselli Proukaki takes a detailed look at the issue of third-State countermeasures, and considers the work the International Law Commission has done in this area. The volume addresses both the theory and practice of third-State countermeasures within international law. Critically reviewing the conclusions of the International Law Commission on the non-existence of a right to third-State countermeasures, it includes consideration of examples of State practice not previously covered in the literature of this topic. In taking a thorough view of the issues involved the author identifies concerns about third-State countermeasures which remain unanswered, and considers the possible legal ramifications arising from a clash between a right to third-State countermeasures and obligations arising from other international norms. The Problem of Enforcement in International Law explores questions evolving around the nature, integrity and effectiveness of international law and the role it is called to play in a contemporary context. This book is of great interest and value not only for specialists in this area of international law, but also human rights, trade and EU lawyers, practitioners, legal advisers, and students.